Fulminant Myocarditis - Wang, Dao Wen.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides readers recent advances on basic research and clinical management of fulminant myocarditis. First chapters introduce aetiology, pathology, and pathophysiology of fulminant myocarditis, in which excessive immune activation and subsequent cytokine storm are proposed to be the core pathogenesis. Following chapters present clinical management of fulminant myocarditis, including clinical manifestations, examinations, and diagnosis of fulminant myocarditis, as well as life support-based comprehensive treatment regimen in acute phase.
Overview of Fulminant Myocarditis -- Aetiology of Fulminant Myocarditis -- Pathology of Fulminant Myocarditis -- Pathophysiology of Fulminant Myocarditis -- Clinical Manifestations of Fulminant Myocarditis -- Lab Tests of Fulminant Myocarditis -- Histological Changes in Fulminant Myocarditis and Their Clinical Association -- ECG Features in Fulminant Myocarditis -- Echocardiography Features in Fulminant Myocarditis -- Cardiac MRI in Fulminant Myocarditis -- Endocardial Biopsy and Necropsy in Fulminant Myocarditis -- Clinical Diagnosis and Differentiations of Fulminant Myocarditis -- Treatment of Fulminant Myocarditis in Acute Phase -- Treatment of Rehabilitation -- Nursing and Caring of Fulminant Myocarditis -- Follow-up and Prognosis of Fulminant Myocarditis -- Typical Cases of Fulminant Myocarditis -- Advances in Basic Research in Fulminant Myocarditis.
Keywords: Cardiology; Cardiology; Myocarditis -- diagnosis; Myocarditis -- etiology; Myocarditis -- therapy; Diagnosis, Differential